(untitled) (Fiep Bulletin - online, 2011)
Introduction: although postoperative pain is experienced by thousands of people around the world every day, it’s only effectively relieved on 30% to 50% of the patients. Because inadequate treatment for postoperative pain can cause unnecessary suffering to patients suffering from it, this is a subject that must be studied. Objective: to identify in literature the actions and interventions that can be performed by the nursing staff in order to relieve postoperative pain. Methodology: the research was performed on textbooks and in the BIREME website, and the inclusion criteria consisted of full texts on the selected theme, published from 2000 to 2009 in Portuguese, Spanish and English. Discussion: nursing interventions on patients suffering from postoperative pain can be pharmacological and non-pharmacological. When programming therapy, more than one of these strategies must be included so satisfactory relief can be achieved. Conclusion: We identified in this research that countless intervention methods are available for the nursing staff to relieve postoperative pain. It’s important to emphasize that each intervention must be adequate to each particular individual and his or her needs.